Psychological flow and its relationship to social responsibility among students of the College of Physical Education and Sports Sciences at the University of Baghdad - Shaker, Asst. Prof. Dr. Laheeb Ahmed (Sulaimani Journal for Humanities, 2026)
Psychological flow is a modern concept in psychology that aims to reinforce the positive aspects of an individual's personality. It represents an important aspect as a reflective experience that occurs when an individual loses themselves in the process of thinking and contemplating in order to find solutions to problems. Social responsibility is also an individual responsibility. No person's personality develops, integrates, and matures except through a connection to the community—a connection based on emotion, attachment, compassion, and awareness. This connection involves belonging, interest, and understanding, and a unity of existence and future. Social responsibility typically arises only from actions performed within a structured social framework. Students in the Faculty of Physical Education and Sports Sciences face numerous psychological pressures and social problems during their studies, training, and participation in sports competitions, which affect their mental well-being. From this perspective, the researcher believes that students should receive the utmost care and attention from society in all aspects: mental, psychological, physical, and emotional. Psychological care empowers them to face challenges and difficulties and enables them to achieve their goals without feeling despair and frustration. This can be achieved by providing positive psychological variables that contribute to prevention. From the pressures and psychological disturbances, they experience happiness and satisfaction while participating in all sports activities. Therefore, the researcher decided to study psychological flow and its relationship to social responsibility among students of the College of Physical Education and Sports Sciences at the University of Baghdad. The research aimed to develop two scales, one for psychological flow and the other for social responsibility, and to identify the nature of the relationship between psychological flow and social responsibility among third-year students at the College of Physical Education and Sports Sciences at the University of Baghdad. The researcher used the descriptive method with a survey approach and correlational relationships, as it was suitable for the research problem. The research population was determined purposively and consisted of third-year students at the College of Physical Education and Sports Sciences at the University of Baghdad, totaling (237) students representing (9) sections. The research sample was selected randomly and consisted of the following sections (A, C, D, F, K, and T), totaling (179) students. The sample was then divided into sub-samples for the purposes of the research as follows: a pilot sample (9), a control sample (100), and a main experimental sample (70). The researcher then proceeded to develop the two scales and applied the established criteria. The scientific method involved developing the axes and sections, conducting statistical procedures and field experiments, and ultimately finalizing the two scales. Following this, the results of the application were analyzed, leading to several conclusions, including that third-year students in the College of Physical Education and Sports Sciences possess strong psychological well-being and social responsibility. The sample demonstrated excellence across various axes and domains. The researcher recommended the adoption of these two scales and the continued development of methods and courses that enhance and cultivate psychological well-being and social responsibility.
Keywords: Psychological flow; social responsibility; students